CLOUD TECHNOLOGY’S IMPACT ON CRM AND FINTECH: A TECHNICAL ANALYSIS - Nethaji Kapavarapu (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This technical article examines the transformative impact of cloud computing on Customer Relationship Management (CRM) and Financial Technology (FinTech) sectors. The article investigates how cloud integration has revolutionized business operations through advanced artificial intelligence, machine learning, and IoT capabilities. The article explores various aspects including blockchain integration, AI-driven analytics, regulatory technology implementation, and security considerations. Through comprehensive analysis of multiple enterprise implementations, the article demonstrates significant improvements in customer retention, operational efficiency, security measures, and regulatory compliance. The article highlights how cloud-based solutions have enabled organizations to process unprecedented volumes of data while maintaining high performance and security standards, ultimately transforming how businesses interact with customers and manage financial operations.